A DECOMPOSITION METHOD FOR THE ELECTROMAGNETIC SCATTERING FROM A CONDUCTIVE OBJECT BURIED IN A LOSSY MEDIUM - Makal, S.; Kizilay, A. (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2011)
A new numerical solution method is presented for the electromagnetic field scattered by a perfectly conducting (PEC) cylindrical object with an arbitrary cross-section buried in a lossy dielectric half-space. The dielectric half-space is considered to be flat, and the method is outlined for TM(z) (horizontally) polarized incident wave. The surface equivalence principle and a decomposition method are utilized to form a set of electric field integral equations (EFIEs) for the currents on the object and the portion of the surface most strongly interacting with the object. To obtain the scattered electric field, the EFIEs are solved in the frequency domain using the method of moments (MoM).
Keywords: Electromagnetic scattering; integral equations; method of moments; perturbational field; DIELECTRIC OBJECTS; MULTIPLE LAYERS; TM SCATTERING; HALF-SPACE; CYLINDER; INTERFACE; Engineering; Telecommunications